A multilayer graph model of the internet topology. (16th March 2020) - Tilch, Georg; Ermakova, Tatiana; Fabian, Benjamin
The application of internet maps for developing more effective routing algorithms, security mechanisms and resilience management for both companies and internet service providers can be advanced through their more detailed structural decomposition. This article carefully integrates traceroute datasets from various large-scale measurement campaigns such as iPlane, CAIDA, Carna, DIMES, RIPE Atlas and RIPE IPv6L into internet graphs of a previously unknown large and thus solid scale. It further works with different well-established abstraction levels such as the IP interface, router, point of presence (PoP), autonomous system (AS) and internet service provider (ISP). Finally, by employing a broad diversity of graph measures, this study creates an exhaustive snapshot of the global internet topology. This work creates a baseline for future internet research. Repeated measurements and automated data integration could enable a better understanding of the internet dynamics.